Small bowel obstruction secondary to Ascaris lumbricoides in the setting of prior exploratory laparotomy - Cynthia Fata; Fouzia Naeem; Erik R. Barthel (Elsevier, 2019)
Ascaris lumbricoides is a parasitic roundworm that is transmitted via the fecal-oral route and is endemic in many areas around the world. At the end of its life cycle it resides in the small bowel, and while it can be asymptomatic, large masses of worms can result in intestinal obstruction, volvulus and perforation. While it is a common cause of mechanical obstruction in endemic areas, it is far less so in the developed world, where adhesions and other postoperative mechanical etiologies are more common. We present the case of a young man with a prior history of exploratory laparotomy for trauma, who had recently immigrated from the Philippines, where ascariasis is endemic, to the Central Valley of California in the United States. He presented with a small bowel obstruction, and at laparotomy was noted to have both a proximal Ascaris bezoar as well as a distal anastomotic stricture.